Root Cause Analysis of Compression-bar Failure on Manual Pontoon Hatch Cover Systems - Arwen Surya Adi Anjalu; Aulia Windyandari; Zulfaidah Ariany; Mohd Ridwan; Tuti Rachmawati Yusuf (International Journal of Marine Engineering Innovation and Research, 2026)
Hatch covers are critical structural components that maintain cargo hold watertightness and operational safety. This study investigates non-conformities in the compression bar of a manual pontoon-type hatch cover on a Gearless Multi-Purpose Vessel constructed at PT. KTU Shipyard. The analysis evaluates construction conditions and the conformity of fabrication and installation processes with MacGregor standards and ClassNK requirements. Root causes were identified using the Root Cause Analysis (RCA) method within a qualitative descriptive case study approach. Data were obtained through visual inspection, manual measurement with an acceptable compression tolerance of 14–24 mm, ultrasonic testing with a leak acceptance limit of <10% OHV, and review of design drawings and technical specifications. RCA was performed using fishbone diagrams and the five-why method, addressing human, method, material, measurement, environment, and machine factors. Findings show that improper installation beyond manufacturer tolerances caused uneven gasket contact pressure, reducing sealing performance. The primary causes were inadequate fabrication and installation practices and inconsistent tolerance verification. Recommended corrective actions include standardizing procedures, strengthening technical competence, and implementing systematic inspection and measurement control at all work stages.